Targeted alpha therapy for glioblastoma - Kunikowska, Jolanta; Morgenstern, Alfred; Pełka, Kacper; Bruchertseifer, Frank; Królicki, Leszek (Frontiers in Medicine, 2022)
According to the World Health Organization 2021 classification of central nervous system tumours, glioblastoma (GB) is a primary brain tumour and presents with the worst prognosis. Because of its infiltrating character, molecular heterogeneity, and only partly preserved function of the blood-brain barrier the median overall survival time is short (9-15 months), regardless of comprehensive treatment including surgery, radio- and chemotherapy. Several novel treatment strategies are under investigation. Unfortunately, none of them with successful results; 90% of patients have recurrence of disease within 6 months. Local administration of drug could be a promising approach to deliver treatment with minimized side effects, as 95% of glioblastomas evince themselves as unifocal lesion recuring within a 2-cm margin at the primary site. Several ligand-receptor systems have been evaluated like targeting tenascin, the extracellular matrix protein, or radiolabelled somatostatin analogues as it is overexpressed with the SSTR-2 receptor system in about 80% of gliomas. Moreover, the study revealed that the NK-1 receptor is overexpressed in GB, so the substance P (SP) can be used as a ligand. A variety of radioisotopes with different physical properties– beta- (131I, 90Y, or 177 Lu), as well as alpha emitters (213Bi, 225Ac or 211At) were tested for treatment. Alpha particles have many advantages over beta radiation like short range with higher linear energy transfer. According to that characteristic, it is an extremely dose delivered to the targeted cells, while reducing harm to nearby healthy tissue. Furthermore, the cell cycle phase, cell oxygenation and O-6-methylguanine-DNA methyltransferase (MGMT) gene promoter methylation status, have no influence on the biological effect of alpha radiation.. In this paper we will summarize experience with local treatment of primary and secondary GB with locally used radioisotopes like [213Bi]Bi-DOTA-SP or [225Ac]Ac-DOTA-SP.